The problem of antibiotic resistance in the treatment of Helicobacter pylori infection - Milivojević, Vladimir (Medicinski podmladak, 2023)
Timely and adequate treatment of Helicobacter pylori (H. pylori) infection is essential, bearing in mind the high prevalence rate (>50%), the fact that infection with this pathogen causes chronic gastritis as well as significant complications in the form of ulcer disease, MALT lymphoma, metaplasia and adenocarcinoma of the stomach. Numerous national recommendations and international guidelines dictate the effectiveness of therapy, but their inconsistent implementation disrupts the cure rate and increases the possibility of developing antibiotic resistance. According to preliminary data, the rate of resistance in Serbia is high. The goal of therapeutic guidelines should be efficient therapy, which is safe and which, if possible, prevents the growing resistance to antibiotics. New diagnostic techniques such as bacterial culture and PCR can facilitate diagnosis and determine antibiotic resistance, which further leads to the possible application of a tailored made therapy that can enable a better cure rate by preventing further antibiotic resistance